Arithmetic Accuracy in Children From High- and Low-Income Schools - Elida V. Laski; Joanna Schiffman; Marina Vasilyeva; Anna Ermakova (SAGE Publishing, 2016)
This study investigated income group differences in kindergartners' and first graders' ( N = 161) arithmetic by examining the link between accuracy and strategy use on simple and complex addition problems. Low-income children were substantially less accurate than high-income children, in terms of both percentage of correctly solved problems and the magnitude of errors, with low-income first graders being less accurate than high-income kindergartners. Higher-income children were more likely to use sophisticated mental strategies than their lower-income peers, who used predominantly inefficient counting or inappropriate strategies. Importantly, this difference in strategies mediated the relation between income group and addition. Examining underlying strategies has implications for understanding income group differences in arithmetic and potential means of remedying it via instruction.